Overview Of The Implementation Of Profit Sharing System In Islamic Commercial Banks In Indonesia - Pratiwi, Putri Hadiyanti; Nazulah, Laili Irfatun; Huda, Qomarul; Nurohman, Dede (IQTISHADUNA, 2024)
Profit-sharing system is a special feature of Islamic banking to be offered to the public as a substitute for interest in conventional banks that are considered to contain elements of usury. Identification of problems based on data and previous research is to review how the application of profit-sharing that is characteristic of Islamic banks as a substitute for usury solution, whether the majority of Muslim Indonesians have made maximum use of the profit-sharing system, and whether Islamic banks carry out their financing activities by Sharia provisions. The purpose of this study was to determine the application of the profit-sharing system in Islamic commercial banks in Indonesia and the comparison of the Mudharabah and Musharakah financing systems with the Murabahah financing margin. This research uses qualitative methods of library research approach (literature study). Data analysis techniques using qualitative data Miles and Huberman models. As a result, the application of profit sharing in 12 Sharia commercial banks (BUS) in Indonesia is greater than the financing of Musharakah financing Mudharabah. Comparison of Mudharabah and Musharakah financing with a profit-sharing system with Murabahah financing, namely as of December 2022, Murabahah financing is still the largest financing in demand by the Indonesian people. This is because financing with a profit-sharing system contains many risks.